HIGHER EDUCATION: Inter-Faith Relations for Transformation - Jeyaraj, Jesudason Baskar (Journal of Dharma, 2006)
Inter-faith relations mean cordial and meaningful relationship among different religious communities. It includes understanding the faith and practices of others, appreciating the good elements in their culture and valuing the contribution of the people of other faiths towards establishing peace and harmony, restoring justice and the rights of people, and working together for the welfare and equality of all. Religions play an important role in building the nation. Religions are not merely limited to an individuals’ faith or set of beliefs and performing rituals. They are closely linked to society, and influence its culture and customs. Religions are powerful in changing the lives of individuals and communities for better or for worse. Leaders of different religions can teach and lead the people to believe and observe superstitions and practise human sacrifices, sati, caste and racial discriminations. They even promote religious and social oppressions. Some of them flare up riots and conflicts between communities and fuel violence and bloodshed. Religions, thus, can threaten the peace and harmony among people and even destroy communities. On the other hand, religions can build a society by teaching good values, liberating people from all sorts of religious, social, and economic oppressions and bringing peace and harmony among communities within a nation. Many of us do not understand the positive and negative power of religions when used by their leaders or politicians for their own gain. A systematic study of religions at home, schools, colleges and the workplace can help the people to know the merits and demerits of religions and to meet the need of building better relations among faith communities. This paper is written to provide information to students who are not specializing in the field of religion, philosophy, or theology but for those who are doing their studies in arts, science, business, technology, etc.